The Interconnection of Written Language and Thinking Process. (Eurasian Journal of Philology Science and Education, 2015)
The article is written due to the fact that the concepts of written language have started to emerge. In spite of the fact that writing is the product of human thought that has emerged on the basis of spoken language,today in connection with strengthening of its social functions that resulted from the strengthening of the state system, actualization of functions as a means of communication, thought creativity, exchange of information, emotions and indicators, »consolidating», »verifying» characteristics as evidence, arguments, it (writing) as a system of reflection of human mind finds powerful dominant character. Therefore the article presents the interconnection of writing and thinking process, writing and consciousness.
Keywords: written language; oral language; thinking; consciousness; inner speech; invariant